Phenotype of a British North Carolina macular dystrophy family linked to chromosome 6q. Issue 10 (1st October 1998) - Reichel, Martin B; Kelsell, Rosemary E; Fan, Joseph; Gregory, Cheryl Y; Evans, Kevin; Moore, Anthony T; Hunt, David M; Fitzke, Fred W; Bird, Alan C
Abstract : AIMS: To document the phenotype of an autosomal dominant macular dystrophy diagnosed as having North Carolina macular dystrophy (NCMD) in this British family, and to verify that the disease locus corresponds with that of MCDR1 on chromosome 6q. METHODS: 37 family members were examined and the phenotype characterised. DNA samples from the affected members, 19 unaffected and five spouses, were used to perform linkage analysis with six microsatellite marker loci situated within the MCDR1 region of chromosome 6q. RESULTS: Every affected family member had lesions characteristic of NCMD, which developed early in life and usually remain stable thereafter. Although fundus changes are evident in the periphery, all tests revealed that functional loss is restricted to the macula. Some patients with large macular lesions had good visual acuity with fixation at the edge of the lesion at 5° eccentricity. Significant linkage to the MCDR1 locus on chromosome 6q was obtained with three marker loci, with a maximum lod score of 5.9 (q = 0.00) obtained with D6S249. CONCLUSION: This family has the typical phenotype NCMD, and the causative gene was linked to the disease locus (MCDR1) on chromosome 6q. Early onset and localisation of the disease to the central macula allow specialisation of eccentric retina in some eyes with resultant good visual acuity.